Response of H. Pylori Eradication Treatment in Patients with Normal and Below Normal Serum Vitamin D Levels - Almani, Suhail Ahmed; Nazia, Shafaq; Shah, Muhammad Iqbal; Kumar, Santosh; Shaikh, Faraz ul Haque (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the response of H. pylori eradication treatment in patients with normal and below normal serum vitamin D levels at medical wards of Liaquat University Hospital, Jamshoro. METHODOLOGY: This retrospective, self-funded study includes data from 100 patients from March - September 2019. Patient with H. Pylori gastritis were included and exclusion criteria was use of Proton Pump Inhibitors or Vitamin D supplements, and H. Pylori eradication therapy in the past 2?months. H. Pylori was confirmed on serology and stool antigen. Patients were given triple regime eradication therapy and then treatment response was observed by stool antigen. Vitamin D levels were tested and participants divided into Sufficient and Deficient groups. The data was then gathered on a predesigned proforma and analyzed using SPSS version 20.0. RESULTS: Total 55% patients were female and 45% were male and belongs to 18 to 60 years of age. The eradication was successful in 62% and unsuccessful in 38%. The mean vitamin D level was lower in the eradication failure population compared to the eradication successful population (12.6±4.31 vs 32.75±6.63; P<0.01). Amongst the treatment failure group, 78.9% (30) of patients were deficient in vitamin D, as compared to 12.4% (20) of patients being vitamin D deficient in treatment successful group. CONCLUSION: Our results demonstrated that vitamin D deficiency is a factor associated with eradication failure of H. pylori infection. KEYWORDS: Helicobacter pylori, serology, stool antigen, eradication therapy, vitamin D.